Sustainable tourism and hotel management in Meacedonia through the use of renewable energy source - Biljana Petrevska; Vlatko Cingoski; Mimoza Serafimova (UTMS Journal of Economics, 2016)
This study aimed to investigate the nature of energy applied in hotel industry in Macedonia. It explored the indicators for resources application in three, four and five star hotels. The data were collected by means of an online survey conducted among 45 managers and department supervisors. It is found that large number of hotels lack measures to reduce the conventional energy use and replace it with renewable sources of energy. Considering the fact that energy use is a substantial cost factor, the modest and restricted application of geothermal energy, biofuels and photocell lightening is extremely alarming for achieving sustainable tourism development. The study concludes that Macedonian hotels although being fully aware of importance of energy efficiency concept, it is not their managerial priority. It further pointed out that the development and operation of sustainable hotels requires properly planned and designed environmental protection practices. Finally, the study recommends that instead of being driven by increased number of tourists regardless the environmental concern, Macedonian hotels should pay attention and become eco-friendly and be focused on applying environmental oriented practices. At the same time, the research poses new challenges that urgently need to be brought to hotel management in the line of achieving sustainable tourism development.
Keywords: Q20; Q40; 330; energy efficiency; environment; eco-hotels; hotel managers; sustainability